A protumorigenic mDia2-MIRO1 axis controls mitochondrial positioning and function in cancer-associated fibroblasts - Cangkrama, Michael; Liu, Huan; Whipman, James; Zubair, Maria; Matsushita, Mai; Di Filippo, Michela; Kopf, Manfred; Innocenti, Metello; Werner, Sabine (Cancer research, 2022)
Cancer-associated fibroblasts (CAF) are key regulators of tumorigenesis. Further insights into the tumor-promoting mechanisms of action of CAFs could help improve cancer diagnosis and treatment. Here we show that the formin mDia2 regulates the positioning and function of mitochondria in dermal fibroblasts, thereby promoting a protumorigenic CAF phenotype. Mechanistically, mDia2 stabilized the mitochondrial trafficking protein MIRO1. Loss of mDia2 or MIRO1 in fibroblasts or CAFs reduced the presence of mitochondria and ATP levels near the plasma membrane and at CAF-tumor cell contact sites, caused metabolic alterations characteristic of mitochondrial dysfunction, and suppressed the secretion of protumorigenic proteins. In mouse models of squamous carcinogenesis, genetic or pharmacologic inhibition of mDia2, MIRO1, or their common upstream regulator activin A inhibited tumor formation. Consistently, co-upregulation of mDia2 and MIRO1 in the stroma of various human cancers negatively correlated with survival. This work unveils a key role of mitochondria in the protumorigenic CAF phenotype and identifies an activin A-mDia2-MIRO1 signaling axis in CAFs with diagnostic and therapeutic potential.Inhibition of mDia2/MIRO1-mediated mitochondrial positioning in CAFs induces mitochondrial dysfunction and suppresses tumor growth, revealing a promising therapeutic strategy to target tumor-stroma cross-talk.